Anti-inflammatory effects of cell-based therapy with tyrosine hydroxylase-positive catecholaminergic cells in experimental arthritis. Issue 2 (2nd December 2013) - Jenei-Lanzl, Zsuzsa; Capellino, Silvia; Kees, Frieder; Fleck, Martin; Lowin, Torsten; Straub, Rainer H
Abstract : Objectives: Studies in rheumatoid arthritis (RA), osteoarthritis (OA) and mice with arthritis demonstrated tyrosine hydroxylase-positive (TH + ) cells in arthritic synovium and parallel loss of sympathetic nerve fibres. The exact function of TH + cells and mode of TH induction are not known. Methods: Synovial cells of RA/OA were isolated and cultured under normoxic/hypoxic conditions with/without stimulating enzyme cofactors of TH and inhibitors of TH. We studied TH expression and release of cytokines/catecholamines. In vivo function was tested by cell therapy with TH + neuronal precursor cells (TH + neuronal cells) in DBA/1 mice with collagen type II-induced arthritis (CIA). Results: Compared with normoxic conditions, hypoxia increased TH protein expression and catecholamine synthesis and decreased release of tumour necrosis factor (TNF) in OA/RA synovial cells. This inhibitory effect on TNF was reversed by TH inhibition with α-methyl-para-tyrosine (αMPT), which was particularly evident under hypoxic conditions. Incubation with specific TH cofactors (tetrahydrobiopterin and Fe 2+ ) increased hypoxia-induced inhibition of TNF, which was also reversed by αMPT. To address a possible clinical role of TH + cells, murine TH + neuronal cells were generated from mesenchymal stem cells. TH + neuronal cells exhibited a typical catecholaminergic phenotype. Adoptive transfer of TH + neuronal cells markedly reduced CIA in mice, and 6-hydroxydopamine, which depletes TH + cells, reversed this effect. Conclusions: The anti-inflammatory effect of TH + neuronal cells on experimental arthritis has been presented for the first time. In RA/OA, TH + synovial cells have TH-dependent anti-inflammatory capacities, which are augmented under hypoxia. Using generated TH + neuronal cells might open new avenues for cell-based therapy.